Agency theory and demand for audit by small businesses - Mustapha, Mazlina; Chia, Hoh Yaen; Ismail, Hashanah (Penerbit Universiti Teknologi Malaysia, 2015)
It is mandatory for small companies in Malaysia to carry out an audit regardless of their size. Only sole proprietors and partnerships are exempted from this audit, as they are enacted under different regulations. This study aims to examine the characteristics of these small businesses and their demand for voluntary audit from the agency theory perspective. The data for the study were obtained from primary sources. About 100 questionnaires were distributed to sole proprietors and partnerships in Malaysia, however only 62 samples were usable for the purpose of the study. Interviews were also conducted to obtain further insight of the variable under study. Independent t-tests were employed to compare the characteristics between the groups. The results of the study indicate that businesses, which have higher managerial ownership among Malaysian small businesses, demand significantly less audit voluntarily compared to those businesses, which have lower managerial ownership. The sole-proprietors also appear to demand significantly less voluntary audit compared to partners in the partnerships. This may be because they view themselves as the monitoring mechanism in their businesses, which reduce the need for audit, as they are also the owners of the businesses. In addition, the result also indicates that businesses, which have more employees, would significantly demand more voluntary audit compared to those with less employees. This result is consistent with agency theory, which posits that as the number of agents (employees) who manage the businesses increases the demand and need for audit would also arise. In addition, the results also suggest that those small businesses, which are larger and have more liabilities would voluntarily demand more audit compared to those, which are smaller and have less liabilities.